A Chemical Analysis of Red Snapper Bone (Lutjanus Sp) Flour - Kaliky, Nurainy (International Journal Labs, 2022)
Background: One way to use this red snapper bone waste is through the process of making red snapper bone meals. This fishbone meal in addition to being used as a mixture of animal feed is also used as a supplement to prevent bone loss in humans. Aim: This study aims to utilize red snapper bone waste in fish bone meal and provide information to the community and the fisheries industry about processing fish bones to have economic value. Method: The method used is an experiment that was performed on red snapper bonefish. Findings: The average water content of fishbone meal is 7.88%% because during the drying process of fish bones a lot of water disappears so that at the time of stenciling and in laboratory tests bone meal has low water content, high ash content is caused by immersion with orange water to remove fat and denature the protein. The water content obtained is low 7.88% so it is safe for long storage and the ash content obtained shows the amount of mineral content in the bone meal so it is very good for consumption.